ASSOCIATION OF VITAMIN D WITH THE COMPONENTS OF THE METABOLIC SYNDROME IN GENERAL POPULATION WITHOUT CARDIOVASCULAR DISEASES. EVA STUDY. (June 2018) - Gomez-Sanchez, M.; Gómez-Sanchez, L.; Gonzalez-Sanchez, J.; Alonso-Domínguez, R.; Agudo-Conde, C.; Recio-Rodriguez, J.; Rodríguez-Martín, C.; Patino-Alonso, M.; Sanchez-Aguadero, N.; De Cabo-Laso, A.; Sanchez-Salgado, B.; Rodriguez-Sanchez, E.; et al.
Abstract : Objective: To analyze the association of vitamin D with the metabolic syndrome (MS) and its components in general population without previous cardiovascular diseases. Design and method: Cross-sectional study of general population without cardiovascular diseases. There were included 360 subjects between 35 and 75 years old (51% female), selected by random sampling stratified by age and gender groups using the Sanitary Card base of 4 urban health centers. The MS was defined following the recommendations of the National Cholesterol Education Program III. The circumference of the waist was measured with a tape measure, blood pressure with an OMRON tensiometer model M10-IT. Plasma glucose, lipid profile and 25 hydroxyvitamin D (25OH-D) were measured in blood. Results: Mean values: age 56.8 ± 14.9 years (with MS = 65.4 ± 12.3 years, without MS = 55.5 ± 14.8 years, p < 0.001); 25OH-D17.90 ± 7.34ng/ml (with MS = 19.73 ± 8.03ng/ml, without MS 26.70 ± 13.34 ng/ml, p < 0.001), without gender differences (p = 0.129). Prevalence of MS and its components: 14.3% (14.9% women, 13.7% men). Blood pressure increased 44.1% (40.0% women, 48.8% men), HDL-cholesterol under 13.4% (14.0% women, 12.7% men), triglycerides increased 14.2% (10.8% women, 18.1% men), abdominal obesity 41.9% (49.7% women, 32.7% men) and glycemia increased 14.6% (11.9% women, 17.9% men). They had values 25OH-D < 20ng/ml 33.6% (44.2% with MS, 31.8% without MS) (p < 0.05), 31% in women and 36% in men (p > 0.05). The presence of MS components had lower OH-D values, or p < 0.05 in HDL cholesterol, triglycerides and glycemia. After adjusting by age and sex, we found positive correlation of 25OH-D with HDL-cholesterol (r = 0.261), negative with glycemia (r = -0.165), waist circumference (r = -0.163 and triglycerides (r = -0.261) No correlation with systolic and diastolic blood pressure. In the logistic regression analysis after adjusting by age and sex, the subjects with MS had an OR = 1.690 (95% CI 0.913–3.130) of having figures of 25OH-D < 20 ng/ml (p = 0.085). Conclusions: Subjects with MS have lower values of 25OH-D and correlates with HDL-cholesterol, triglycerides, glycemia and waist circumference. Subjects with MS have 1.7 times more risk of having 25 OH-D < 20 ng/ml.